Pengaruh Kompetensi dan Lingkungan Kerja Terhadap Kinerja Pegawai Bagian Umum Sekretariat Daerah Kota Parepare - Mahyuddin, Fatmawati; Masnaeni, Yunita; Bintoro, Yusran Adi; Palintan, Andi Faiz Fitra Amor; Palobo, Andini Fika Putri (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
In a government agency, employee performance is a determining factor for the success of a good service. In building employee performance, competency, and work environment are required. This study aimed to determine the effect of competence and work environment partially and simultaneously on the performance of employees at the General Section of the Regional Secretariat of Parepare City. This research was conducted at the General Section of the Regional Secretariat of Parepare City. The sample used was the employees of the General Section of the Regional Secretariat of Parepare City, with as many as 47 respondents. The data analysis techniques used in this research are the validity test, reliability, classical assumptions, multiple linear regression, coefficient of determination, t-test, and F test. Based on the results of the study, competence, and work environment have a positive and significant effect on the performance of the general staff of the Parepare City Regional Secretariat, both partially and simultane.